How Africa Got into a Mess: Colonial Legacy, Underdevelopment, Corruption and Human Rights Violations in Africa - Mekoa, Itumeleng (Journal of Reviews on Global Economics, 2019)
The political independence that the people of Africa attained over the last four decades was not a gift from the Western colonial powers. It was however the result of the struggles of the African people against foreign domination and exploitation. The political independence of Africa however did not yield good results for African people. The colonial powers having looted the African continent and its rich natural resources left Africa an empty shell. The independence of Africa could not lead to genuine development of the former colonies. To change the state of affairs which Frantz Fanon describes as "The wretched of the earth", has forced African people into a new form of domination, called neoâ€‘colonialism in various forms. This new form of colonial domination was defined by the All African People’s Conference (AAPC) which took place in 1962 in Cairo as ’the survival of the colonial system in spite of formal recognition of political independence in emerging countries which became the victims of an indirect and subtle form of domination by political, economic, social, military or technical means’ (Machyo 1996:35). It was also pointed out that this new form of foreign domination was the greatest threat to African countries and sovereignty. The reason being that the neoâ€‘colonial powers had the tendency to resort to ’economic and political intervention in order to prevent African leaders from directing their political, social and economic policies towards the exploitation of their people and their natural resources. The problems of modern Africa in the post-colonial period are a mockery for the so-called independent or liberated Africa. The conditions of the African people are worse than they were in the colonial period. However other problems of Africa were not of colonial design but African design like under-development, corruption and human rights violations. The purpose of this article is to examine the problems plaguing post-colonial Africa.